2013
DOI: 10.1097/icl.0b013e31828af147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multipurpose Solutions on the Viability and Encystment of Acanthamoeba Determined by Flow Cytometry

Abstract: These results suggest that viability and encystment of Acanthamoeba are independent phenomena, and therefore disinfecting efficacy of MPS and encystment rates of Acanthamoeba should be evaluated, respectively. Thus, it is important to evaluate simultaneously the disinfecting efficacies and encystment rates of newly developed premarket MPS using the authors' novel flow cytometric methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In this endeavor, we have analyzed the antimicrobial activity of a wider range of marketed CLC products than other recent method advancement attempts [12,14]. Further, this novel method development examines more individual strains of Acanthamoeba within one body of work, which are the most common pathogens associated with AK and are strains that are well-established laboratory and clinical strains thoroughly described in the literature [20][21][22], which is more than other method development attempts [12,14,15,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this endeavor, we have analyzed the antimicrobial activity of a wider range of marketed CLC products than other recent method advancement attempts [12,14]. Further, this novel method development examines more individual strains of Acanthamoeba within one body of work, which are the most common pathogens associated with AK and are strains that are well-established laboratory and clinical strains thoroughly described in the literature [20][21][22], which is more than other method development attempts [12,14,15,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Trypan Blue staining methods depend solely upon a hemocytometer cell count, and thus, are less accurately quantified [30]. Additionally, it must be stated that staining methods that involve flow cytometry depend on cell permeability to dyes to facilitate accurate counting, which are difficult to accurately align with the use of flow and have failed to appropriately address trophozoite permeability in the presence of biocides [23,24,31]. Most importantly, to our knowledge, none of these methods can be or were directly compared to widely-reported testing methods to ensure an equal comparison, indicating a major flaw of method development so far.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, in 2007 an outbreak of Acanthamoeba keratitis, was linked to use of Complete MoisturePlus (AMO, Santa Ana, CA). Laboratory investigations later revealed that a component of the solution, proplylene glycol, induced encystment of Acanthamoeba trophozoites, potentially rendering the organism more resistant to disinfection …”
Section: Epidemiology Of Acanthamoeba Keratitismentioning
confidence: 99%
“…Laboratory investigations later revealed that a component of the solution, proplylene glycol, induced encystment of Acanthamoeba trophozoites, potentially rendering the organism more resistant to disinfection. [109][110][111][112] Following the recall of Complete MoisturePlus, there was a drop in the number of cases in the US, however this decrease did not reach the low level prior to the product launch. 113 There seemed to be some residual increased risk that was not present in the early 2000s.…”
Section: Contact Lens Solutions and Their Usementioning
confidence: 99%
“…AK is a sight-threatening condition, and outbreaks have been linked to specific contact lens solutions ( 3 ), hard water with lime scale ( 4 ), and biofilm contamination of domestic and recreational water ( 5 , 6 ). The expanding problem of algal bloom and nutrient pollution in Iowa waters might also be contributing to an increase in pathogenic Acanthamoeba species and the rising number of AK cases ( 6 ).…”
mentioning
confidence: 99%